Collaborative Governance Dalam Program Perhutanan Sosial Pada HKm Gempa 01 Kurau Barat Bangka Belitung - Satria, Bambang Ari; Hermianto, Hermianto (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2020)
Forest governance by the people is a new approach in social forestry. Utilization and management of social forestry in the Province of Bangka Belitung Islands is carried out in order to provide access for the community to manage forests sustainably to improve community welfare. One of them is Community Forest (HKm) Earthquake 01 West Kurau, Bangka Belitung. This research is entitled collaborative governance in the utilization of social forestry in the HKm Gempa 01 West Kurau Bangka Belitung. This study aims to determine how the implementation of collaborative governance in the use of social forestry in the HKm Gempa 01 West Kurau Bangka Belitung. The theory used is the theory of collaborative processes by Chris Ansell and Alison Gash. This study used qualitative research methods. Data collection techniques using interviews, observation and audio visual. The results showed that the collaborative process between stakeholders involved in the social forestry program at HKm Gempa 01 West Kurau Bangka Belitung had gone well. This is marked by the increasing ecological impact and economic impact on the community in West Kurau Village through the use of social forestry programs and the achievements of HKm Gempa 01 Kurau Barat as 1st winner at the national level in the Community Forest category in 2019.